STRATEGI PEMASARAN, KEPUASAN KONSUMEN DAN KINERJA BISNIS DI KARTIKA JAYA KABUPATEN KENDAL, JAWA TENGAH (Studi Deskriptif Kualitatif Strategi Pemasaran dan Rencana Pengembangan Di kartika Jaya Kabupaten Kendal, Jawa Tengah) - Henry Yuliamir; Enik Rahayu (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2021)
Kartikajaya Village is part of the Wonosari village area, before it became its own village known as Bleder. At that time it was still in the form of forests and swamps and was often used for TNI war games, especially Soldiers of the VII Military Command (now Kodam IV Dipenogero). Kartikajaya Village means the village is Resetement (Prokiamad) which is inhabited by retired TNI AD. It is one of the efforts. Located approximately 9 km from Kendal City, and approximately 10 km from the City of Patebon. Transportation that can be used is angkudes no. 3 and gig by day, and motorcycle taxi at night. When it was first formed this village was a local transmigration site for veterans of the war for independence, so that almost part of the population was retired soldiers. Now, along with the development of the region, the population of Kartika Jaya Village has begun to be heterogeneous in terms of livelihoods, from farmers, fishermen, factory workers, to private employees and civil servants. This research is a qualitative research. The data used in this study were obtained from interviews with Kartika Jaya residents and consumers and the results of the performance were analyzed to obtain a corrective action plan. In general, this study concludes that Kartika Jaya serves the market segment for young people and modern productive age and has a development plan that focuses on consumers (Customer oriented) and the voice of consumers who are very satisfied and satisfied with the performance of the marketing business produced by Kartika Jaya tourism.